Errington owner names manager (Raton Range Raton, NM, 1980)
This article is about owner Barie P. Fritz naming Leroy C. Rogers the manager of Errington Memorial Chapel
Master list item #: 104
File location is in the Raton file Cabinet
Newspaper article + Photograph of Leroy C. Rogers
Keywords: Rogers, Leroy C; Rogers, Cleo; Rogers, Larry H; Rogers, Terry Lee; Leger, Claudine Rogers; Fritz, Barie P; Alderete, Victor; Vargas, Sam; Errington Memorial Chapel; Ballard Funeral Home; Rogers Mortuary; Business History; Local Business; New Managers; Funeral Homes; Raton, New Mexico